2007
DOI: 10.1093/condor/109.4.862
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Accumulation in European Starlings Nesting in a Selenium-Contaminated Environment

Abstract: I compared selenium (Se) levels in blood, liver, egg, and diet samples from European Starlings (Sturnus vulgaris) nesting at Kesterson Reservoir, Merced County, California and the surrounding area. Concentrations were highest in adult and nestling blood (8.3 and 5.5 µg g−1, respectively), nestling liver (7.5 µg g−1), and eggs (4.6 µg g−1) from nest boxes in interior parts of Kesterson compared to those from the perimeter (adult and nestling blood  =  4.0 and 1.4 µg g−1, respectively, nestling liver  =  4.7 µg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Except for nesting or burrowing arthropods, such as ants and some spiders, which remain relatively sedentary over longer periods, it is very likely that several insects analyzed may have been travelling between habitats in search of food. Overall concentrations for arthropods reported in our study are similar to those found in previously sampled invertebrates from this habitat (Santolo and Yamamoto, 1999;Santolo, 2007). Several studies have investigated the impacts of disturbance on ant diversity (Hoffmann and Andersen, 2003 [and references therein]).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Except for nesting or burrowing arthropods, such as ants and some spiders, which remain relatively sedentary over longer periods, it is very likely that several insects analyzed may have been travelling between habitats in search of food. Overall concentrations for arthropods reported in our study are similar to those found in previously sampled invertebrates from this habitat (Santolo and Yamamoto, 1999;Santolo, 2007). Several studies have investigated the impacts of disturbance on ant diversity (Hoffmann and Andersen, 2003 [and references therein]).…”
Section: Discussionsupporting
confidence: 87%
“…The use of the reservoir as a repository for drainage water was then terminated and the ponds were filled in and the vegetation plowed in an effort to prevent further exposure to wildlife. Scientists have continued to monitor wildlife in the area, with most studies focusing on birds and small mammals (Ohlendorf et al, 1988;Santolo, 2009Santolo, , 2007. A few publications have reported on the accumulation of selenium by invertebrates at Kesterson (Ohlendorf, 2002;Ohlendorf et al, 1988;Santolo and Yamamoto, 1999;Santolo, 2007), but no published information is available as to the impact on ants, pollinators, or terrestrial insects at the population or community level.…”
Section: Introductionmentioning
confidence: 99%
“…Plant [ (Santolo 2007) were used to describe the relation between passerine diet and blood Se concentrations (r 2 = 0.47, n = 9, P = 0.042). In addition, we assumed that Se uptake from plant and invertebrate diets was less than complete and used an initial correction factor of 0.70.…”
Section: Resultsmentioning
confidence: 99%
“…Concentrations were similar to or well below levels of 10 elements tested and were ruled out as a likely cause of beak deformities among the endangered southwestern willow flycatcher ( Empidonax trailli extimus ) . For selenium, however, the relationship between liver concentrations in adults and nestlings and concentrations in eggs has been found to be quite variable , so confirmatory testing for inorganic elements in chickadee eggs would more conclusively rule out any effects. The highly toxic, sometimes teratogenic, organic form of mercury (MeHg) was detected in only 3 of 9 adult chickadees tested, and levels were 100‐fold lower than background concentrations measured in liver tissue of other North American passerines and well below concentrations demonstrated to cause chronic or lethal effects in birds .…”
Section: Discussionmentioning
confidence: 99%